Polskie badania nad krytyką literacką Vladimira Nabokova - Karwacka, Monika (Acta Polono-Ruthenica, 2018)
The paper presents development of studies on Lectures on Russian Literature by Vladimir Nabokov in Russia, America and on this background in Poland. Works of Nabokov arouses constant interest among researchers all over the world, however, Nabokov’s literary-critical heritage remained out of scientific focus for a long time until publishing Lectures on literature and later Lectures on Russian literature first in the USA and then in Russia and Poland. In the paper there is presented the attempt to determine the scale and significance of studies on literary-critical works of Nabokov in different countries and to show similarities and discrepancies in international researches.